The Role of Religion in Transcendent Philosophy - Sayyed Meysam Beheshtynezhad (پژوهشنامه فلسفه دین, 2014)
Mullā Sadrā declares that he is so affected by religion and intuition in his philosophy. His claims show that a number of his innovations in different subjects in his philosophy are achieved in the light of religious beliefs as well as intuitive knowledge. In this paper, I aim to probe into how and how much religion has made a role in his philosophy. His declarations show that he has experienced a kind of an existential transcendence at least two times during his life under the influence of religious beliefs and intuitions. Besides, we can show that his philosophy also has transcended twice. So, we will be able know how basically Mullā Sadrā’s philosophy is affected by religion. After each of these stages, Mullā Sadrā has faced with a new paradigm which basically differs from the previous one. It would be surprising to know that Mullā Sadrā has claimed that despite these affections he has not broken philosophical rules at all. We want to know if we can testify this claim.